Implementation of Project-Based Center Learning Model in Kindergarten - Rocmah, Luluk Iffatur; Ma’ruf , Saffaanah Rahma; Ramadhani, Laila Al; Aliffiandi, Rizca Aulia (Procedia of Social Sciences and Humanities, 2024)
This article discusses the viewpoint of the Project-Based Center Learning Model which was carried out at Aisyiyah 4 Pondok Jati Kindergarten, Sidoarjo. The right learning model is the determinant of learning success. Learning that suits the needs of children is learning that can optimally develop children's multiple intelligences. The Center Learning Model is one of the effective approaches because it stimulates all aspects of child development through directed play. This research is motivated by the importance of early childhood education as a foundation in shaping and developing children's character from an early age. The purpose of this study is to answer questions about the application of the center learning model in Aisyiyah 4 Pondok Jati Kindergarten